The Philosophy Of Sunan Gunung Jati’s Petatah-Petitih: The Contributions To Kuwu Ethical Leadership In Cirebon Regency - Subhan Subhan; Ahmad Sururi (IBDA` : Jurnal Kajian Islam dan Budaya, 2021)
This study is focused on the philosophy of Sunan Gunung Jati's petatah-petitih (proverb) and the contribution to the Kuwu (leaders at the local government structure/ village chief) ethical leadership in Cirebon Regency. The material object of this study covers the philosophy of petatah-petitih written by Sunan Gunung Jati while the formal object is social philosophy concerning the local culture. This phenomenological study aims to uncover the insight of Sunan Gunung Jati's philosophy and social phenomena that explain the research problem. This study seeks to examine three things: (1) what is the philosophy of Sunan Gunung Jati's petatah-petitih?, (2) how is the ethical leadership of Sunan Gunung Jati?, and (3) What are the contributions of the philosophy of petatah-petitih to Kuwu ethical leadership in Cirebon Regency?. The findings of this study underline the strong influence of Sunan Gunung Jati's petatah-petitih to the leaders at the local government structure in Cirebon Regency. The moral values in the Sunan Gunung Jati's leadership system are implied in the petatah-petitih and leadership behaviors. The values of the petatah-petitih encompass noble teachings that must be possessed by a leader. The values are broadly categorized into four groups, namely the teachings on faith and devotion, teachings on wisdom, teachings on discipline, and teachings on manner and politeness. These four teachings can be grouped into philosophical ethics in the form of theistic ethics, personal ethics, and social ethics.